Practical implications of naloxone knowledge among suburban people who use opioids - Kristin E. Schneider (Harm Reduction Journal, 2021)
Abstract Background Naloxone distribution programs have been a cornerstone of the public health response to the overdose crisis in the USA. Yet people who use opioids (PWUO) continue to face a number of barriers accessing naloxone, including not knowing where it is available. Methods We used data from 173 PWUO from Anne Arundel County, Maryland, which is located between Baltimore City and Washington, DC. We assessed the prevalence of recently (past 6 months) receiving naloxone and currently having naloxone, the type(s) of the naloxone kits received, and the perceived ease/difficultly of accessing naloxone. We also assessed participants knowledge of where naloxone was available in the community. Results One third (35.7%) of participants had recently received naloxone. Most who had received naloxone received two doses (72.1%), nasal naloxone (86.9%), and education about naloxone use (72.1%). Most currently had naloxone in their possession (either on their person or at home; 78.7%). One third (34.4%) believed naloxone was difficult to obtain in their community. Only half (56.7%) knew of multiple locations where they could get naloxone. The health department was the most commonly identified naloxone source (58.0%). Identifying multiple sources of naloxone was associated with being more likely to perceive that naloxone is easy to access. Discussion Our results suggest that additional public health efforts are needed to make PWUO aware of the range of sources of naloxone in their communities in order to ensure easy and continued naloxone access to PWUO.